Kinematic quantification of gait asymmetry in patients with peroneal nerve palsy based on bilateral cyclograms - Kutilek, P; Viteckova, S; Svoboda, Z; Smrcka, P (Journal of musculoskeletal & neuronal interactions, 2013)
Nowadays, bipedal walking is undergoing extensive study. Several methods can be used in physiotherapeutic research for identifying defects in bipedal walking as a result of pathology of the musculoskeletal or nervous system. Our work focuses on studying asymmetry of walking based on synchronized bilateral knee-knee cyclograms. Participants presenting with peroneal nerve palsy and foot drop were included in the study. The bilateral cyclograms, also called angle-angle diagrams, were created to quantify gait asymmetry before and immediately after application of a brace. In order to quantify the asymmetry of human walking, we have described and tested the application of the method based on the inclination angle of the synchronized bilateral cyclograms. The symmetry index (SI) was used as a comparative method to evaluate the symmetry of bipedal walking. The method based on the orientation of the cyclograms can be used as an additional method for determining the gait asymmetry. The new technique has never been applied before to study the gait asymmetry in patients with peroneal nerve palsy or patients with leg brace.
Keywords: koleno; biomechanika; neuropatie nervus peroneus; algoritmy; Paralysis; Algorithms; chůze (způsob); Biomechanical Phenomena; Middle Aged; mužské pohlaví; Adult; ženské pohlaví; Humans; Peroneal Neuropathies; Food; Knee; lidé středního věku; dospělí; Female; Gait; potraviny; lidé; Male; paralýza